Unrestrained measurement of arm motion based on wearable wireless sensor network - Lee, Guo Xiong (2011)
Techniques that could monitor human motion precisely are useful in applications such as rehabilitation, virtual reality, sports science and surveillance. Most of the existing systems require wiring that restrains the natural movement. To overcome this limitation, a wearable wireless sensor network using accelerometers has been developed in this study to determine the arm motion in the sagittal plane. The system provides unrestrained movements and improves its usability. The lightweight and compact size of the developed sensor node makes its attachment to the limb easy. Experimental results have shown that the system has good accuracy and response rate when compared to a goniometer.